Elaboração da carta geotécnica de suscetibilidade de um trecho da rodovia marechal rondon - sp-300 (SP, Brasil) - Fernandes, Francely Martinelli [UNESP]; Cerri, Leandro Eugenio da Silva [UNESP] (My University, 2011)
The highways are enterprises of great longitudinal extension that cross several types of lands, that possess different geologic, geomorphologic, pedologic and vegetation conditions. In the environmental management of highways the importance of the use of Engineering Geological Maps of Susceptibility was noticed, for being documents that inter-relates several information of the environment. This way, this research objectified the elaboration of this type of map and the indication of lines of direction for the conservation of the Highway Marechal Rondon - SP-300. For its elaboration the Map of Declivity, the delimited Homogeneous Physiographic Units, the processes of the superficial dynamics mapped and the use of the ground was used. Its elaboration evidenced its importance for the environmental management of highways, in view of the prevention, the monitoring and the correction of the adverse processes that can occur in this type of enterprise.

As rodovias são empreendimentos de grande extensão longitudinal que atravessam diversos tipos de terrenos, que possuem condições geológicas, geomorfológicas, pedológicas e vegetacionais diferenciadas. A utilização de Cartas Geotécnicas de Suscetibilidade é de grande importância na gestão ambiental de rodovias, por serem documentos que inter-relacionam diversas informações do meio físico. Desta forma, esta pesquisa objetivou a elaboração da carta geotécnica de suscetibilidade aos processos da dinâmica superficial e a indicação de diretrizes para a conservação da Rodovia Marechal Rondon – SP-300. Para sua elaboração foram utilizados o Mapa de Declividade, as Unidades Fisiográficas Homogêneas delimitadas, os processos da dinâmica superficial mapeados e o uso do solo. Sua elaboração evidenciou sua importância para a gestão ambiental de rodovias, tendo em vista a prevenção, o monitoramento e a correção dos processos adversos que podem ocorrer neste tipo de empreendimento. Palavras-chave: cartografia geotécnica, erosão, movimentos de massa, gestão ambiental.
Susceptibility engineering geological map elaboration of marechal rondon road stretch - sp-300 (SP, Brazil)
Keywords: Engineering geological mapping; Environmental management; Erosion; Mass movements; engineering geology; environmental management; erosivity; geological mapping; geomorphology; land use planning; longitudinal gradient; mass movement; motorway; pedology; vegetation type; Brazil; Sao Paulo [Brazil]